Potensi Usaha Jasa Penyewaan Peralatan Bayi dan Anak di Kota Palangka Raya - Oktanasari, Dewi Putri; Lisnawati, Lisnawati; Jelita, Jelita (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The baby and children's equipment rental business can be said to have great potential in Palangka Raya City. This research is very important to study considering that rental of baby and children's equipment in Palangka Raya City is starting to develop, even though the number of existing rental businesses is still very minimal. The type of research used in this research is field research. This research approach uses a descriptive qualitative approach. This research was conducted in two locations, the first at Alisya Baby Rental, the second at Adinda Rental Palangkaraya. The subjects of this research were shop owners at two rental shops. The data collection techniques used were observation, interviews and documentation. Baby and children's equipment rental services can be a source of income and are not yet widely pursued in Palangka Raya City, so baby and children's equipment rental services have huge business opportunities. Before opening a baby and children's equipment rental service business, things you must pay attention to are equipment data, capital and profits.